Decisive role of non-rare earth metals in high-regioselectivity addition of μ3-carbido clusterfullerene. Issue 21 (22nd September 2022) - Chen, Muqing; Zhao, Yaoxiao; Jin, Fei; Li, Mengyang; Guan, Runnan; Xin, Jinpeng; Yao, Yang-Rong; Zhao, Xiang; Wang, Guan-Wu; Zhang, Qianyan; Xie, Su-Yuan; Yang, Shangfeng
Abstract : The reaction of μ 3 -CCF Dy2 TiC@ I h -C80 with AdN2 affords only one [6, 6]-open monoadduct along with the addition sites adjacent to the Ti 4+ ion instead of the two Dy 3+ ions, revealing the decisive role of the non-rare earth metal Ti(IV). Abstract : Endohedral clusterfullerenes featuring encapsulation of metal clusters which transfer electrons to the outer fullerene cages show intriguing chemical properties different from empty fullerenes. Despite the extensive studies on the chemical properties of empty fullerenes, especially C60, chemical functionalization of endohedral clusterfullerenes has been less explored, and previous reports are primarily limited to the well-known metal nitride and carbide clusterfullerenes. Herein, we report the first chemical functionalization of an emerging endohedral clusterfullerene μ3 -carbido clusterfullerene (abbreviated as μ3 -CCF) bearing central μ3 -C and Ti(iv ) atoms forming a TiC double bond. A μ3 -CCF Dy2 TiC@ I h -C80 is synthesized, and its molecular structure is unambiguously determined by single-crystal X-ray diffraction for the first time. A photochemical cycloaddition reaction of Dy2 TiC@ I h -C80 with 2-adamantane-2, 3-[3 H ]-diazirine (abbreviated as AdN2 ) is then carried out and only one monoadduct Dy2 TiC@ I h -C80 -Ad is obtained, indicating its high regioselectivity. According to the X-ray single-crystal structure of Dy2 TiC@ I h -C80 -Ad, the Ad moiety selectively attacks the [6, 6]-bond (conjunction of two fused hexagons), which is adjacent to the Ti 4+ ion instead of the two Dy 3+ ions, affording a [6, 6]-open addition pattern. Theoretical calculations unveil that the Ti(iv ) ion plays a decisive role in high regioselectivity, and the formation of [6, 6]-open Dy2 TiC@ I h -C80 -Ad is thermodynamically preferred. Contrarily, a similar reaction of a Ti(iii )-containing nitride clusterfullerene Y2 TiN@C80 with AdN2 is predicted to generate a different type of adduct with the addition sites adjacent to the Y 3+ ion instead of the Ti 3+ ion. This reveals the peculiarity of the chemical property of μ3 -CCF resulting from the existence of the non-rare earth metal Ti with a high oxidation state.